Pathophysiology and inflammatory biomarkers of sulfur mustard-induced corneal injury in rabbits. - Dinesh G Goswami (Public Library of Science (PLoS), 2021)
Sulfur mustard (SM) is a cytotoxic, vesicating, chemical warfare agent, first used in 1917; corneas are particularly vulnerable to SM exposure. They may develop inflammation, ulceration, neovascularization (NV), impaired vision, and partial/complete blindness depending upon the concentration of SM, exposure duration, and bio-physiological conditions of the eyes. Comprehensive in vivo studies have established ocular structural alterations, opacity, NV, and inflammation upon short durations (<4 min) of SM exposure. In this study, detailed analyses of histopathological alterations in corneal structure, keratocytes, inflammatory cells, blood vessels, and expressions of cyclooxygenase (COX)-2, matrix metalloproteinase (MMP)-9, vascular endothelial growth factor (VEGF), and cytokines were performed in New Zealand white rabbits, in a time-dependent manner till 28 days, post longer durations (5 and 7 min) of ocular SM exposure to establish quantifiable endpoints of injury and healing. Results indicated that SM exposure led to duration-dependent increases in corneal thickness, opacity, ulceration, epithelial-stromal separation, and epithelial degradation. Significant increases in NV, keratocyte death, blood vessels, and inflammatory markers (COX-2, MMP-9, VEGF, and interleukin-8) were also observed for both exposure durations compared to the controls. Collectively, these findings would benefit in temporal delineation of mechanisms underlying SM-induced corneal toxicity and provide models for testing therapeutic interventions.